OTHER WAYS TO BUILD CORRELATION MODELS - Sh. B. Ochilov; A. N. Tagaev; O. K. Khudayberdieva (Research Parks Publishers, 2021)
This article has developed a new method for building production functions. On the basis of accurate data, the methodology for calculating the coefficients of any mathematical models is shown.